1997
DOI: 10.1515/znc-1997-11-1215
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Flavones from Scutellaria baicalensis in Lecithin Liposomes

Abstract: Trihydroxyflavones of Scutellaria baicalensis, Antioxidant Activity, Liposome, Peroxidation, MDA The antioxidant effect of a trihydroxyflavone extract from Scutellaria baicalensis on oxida­ tion induced by ultraviolet light, was studied with phosphatidylcholine liposome membrane. Also, as standards, the antioxidative activity of baicalin, wogonin, baicalein and butylated hydroxytoluene (BHT) was investigated. Comparison of the protective effects of thecom­pounds studied against photoinduced lipid peroxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…The flavonoids contained in S. baicalensis have also strong anti-oxidant properties [71]. An extract from this plant was shown to possess protective activity against oxidation induced by UV light [72][73][74] and it could be used as an additive in cosmetic products for UV protection [75]. Moreover, it was shown that topical baicalin application mitigates DNA photo-damage [76] and baicalein exerts anti-ageing effects through attenuating oxidative stress [77].…”
Section: Discussionmentioning
confidence: 99%
“…The flavonoids contained in S. baicalensis have also strong anti-oxidant properties [71]. An extract from this plant was shown to possess protective activity against oxidation induced by UV light [72][73][74] and it could be used as an additive in cosmetic products for UV protection [75]. Moreover, it was shown that topical baicalin application mitigates DNA photo-damage [76] and baicalein exerts anti-ageing effects through attenuating oxidative stress [77].…”
Section: Discussionmentioning
confidence: 99%
“…27 In brief, the lipid (egg phosphatidylcholine, sphingomyelin and cholesterol) with an appropiate amount of fluorescent probe were mixed in chloroform. After removing solvent, the dry lipid film was hydrated with 140 mM NaCl with phosphorane buffer at pH 7.4 (PBS).…”
Section: Liposome Preparation and Fluorescence Measurementsmentioning
confidence: 99%
“…Egg lecithin in chloroform was dried under vac uum in a nitrogen atmosphere (Gabrielska et al, 1997). A 0.05 m M Tris:HCl [(hydroxymethyl) aminomethane] buffer of pH 7.4 was added and the sample was shaken for 15 min (control sam ple), and after adding the appropriate anthocyanin extracts for another fifteen min.…”
Section: Induction O F Lipid Peroxidationmentioning
confidence: 99%
“…Egg lecithin was mixed with an appropriate amount of anthocyanin extract in chloroform, dried under vacuum in a nitrogen atmosphere (Gabrielska et al, 1997), and hydrated with a 0.05 m M TrisrHCl [(hydroxymethyl)aminomethane] buffer, pH 7.4. The sample was than shaken for 15 min.…”
Section: H P L C Analysis O F 2-hydroxy Pyrimidine (Reaction O F Malomentioning
confidence: 99%